Hanoi - Toward A Water Pollution and Flood Free City - World Bank (World Bank, Washington, DC, 2020)
Hanoi has grown rapidly into a modern, vibrant city. However, the development of infrastructure and services has lagged behind the growth of the population. In particular, two significant water-related problems have arisen. Water pollution has become a major issue, creating a huge environmental and public health hazard, impairing the liveability of the city, deterring investors, and compromising downstream agriculture and the ecological integrity of the river system. Flooding is also becoming a major problem in many districts, occurring whenever there is a cloudburst. The city’s master plan addresses these two challenges of pollution and flooding but implementation has not kept pace with the growth of the problems. To support an effective implementation of the master Plan, the World Bank supported Hanoi City to study the problem of pollution in selected hotspots with a focus on the four main rivers running through the city and the problem of urban flooding in two key districts. This policy note draws on the findings and recommendations of the World Bank-financed technical assistance to the city. This study is also in line with the World Bank’s ongoing collaboration with the government of Vietnam to help develop strategies and to identify the fundamental shifts needed to achieve national water security.